H∞ control for time-delay systems with randomly occurring nonlinearities subject to sensor saturations, missing measurements and channel fadings. (April 2018) - Ji, Huihui; Zhang, He; Li, Chenlong; Senping, Tian; Lu, Junwei; Wei, Yunliang
Abstract: The H ∞ control problem for a class of time-delay systems with randomly occurring nonlinearities (RONs) is addressed in this paper. Sensor saturations, missing measurements and channel fadings are governed by random variables obeying the Bernoulli distributions. The measurement output is subject to both data missing and randomly occurring sensor saturations (ROSSs) described by sector-nonlinearities as well as the channel fadings caused typically in wireless communication. The aim of the addressed problem is to design a full-order dynamic output-feedback controller such that the closed-loop system is exponentially mean-square stable and satisfies the prescribed H ∞ performance constraint. Sufficient conditions are presented by resorting to intensive stochastic analysis and matrix inequality techniques, which not only guarantee the existence of the desired controller for all possible time-delays, RONs, missing measurements and ROSSs but also lead to the explicit expressions of such controllers. Finally, a numerical example is given to demonstrate the applicability of the proposed control scheme. Highlights: H∞ control problem is studied for delayed systems with RONs subject to ROSSs, missing measurements and channel fadings. The proposed system is general enough to model the phenomena of RONs, ROSSs, missing measurements and channel fadings. A new energy-like function is employed to analyze exponential mean-square stability and H∞ performance of the system. Intensive stochastic analysis is conducted to enforce H∞ performance for the system. The main results in Theorem 2 contain all information about system parameters and features.